CHARACTERISTIC OF RARE EARTH ELEMENT IN SEDIMENT AT COASTAL AND OFFSHORE AREA OF KUNDUR ISLAND, RIAU PROVINCE - Deny Setiady; I Wayan Lugra (BULLETIN OF THE MARINE GEOLOGY, 2013)
The study area is located at coastal and offshore Kundur and Adjacent Area, geographically located at coordinates of 0Âº 39'00 "0Âº 50'00" N and 103Âº 10'00 "103Âº 25 '00" S. Rare earth elements are found in seven seafloor surfacial sediment and 3 core samples are Cerium (15.41 to 16.88 ppm), Lanthanum (5.40 to 6.80 ppm), Ytrium (5.18 to 5, 58 ppm), Zirconium (5.05 to 5.95 ppm) and Neodymium 20.25 to 20.95 ppm). The minerals that containing of rare earth elements at the study area are apatite, zircon, monazite, and pyrochlore and xenotime. Seafloor surfacial sediment at Kundur are composed by silt (Z), sandy silt (sZ), sandy gravel, mud and sand. Silt unit covering nearly 55% of the study area and followed by sandy gravel, sand, silt and sandy silt. Seafloor morphology varies those are flat morphology with gradually depth changes and a regularly shaped identation curves and holes likely a result of sand mining. Coastal characteristics consists of: sandy and muddy beach. Sandy beach has medium relief (5Â° - 8Â°), composed by medium to coarse sand, brownish yellow. The muddy beach has low relief (1Â° - 5Â°) where the edges of the beach is mangroves planted by the local peoples. Key words : rare earth elements, seabed sediments, sea floor morphology, and Kundur Island Daerah penelitian terletak di kawasan pantai dan lepas pantai perairan Pulau Kundur dan Sekitarnya. Secara geografis terletak pada koordinat 0Âº 39â€™00â€ - 0Âº 50'00â€ LU dan 103Âº 10'00â€- 103Âº 35' 00â€BT. Mineral di daerah penelitian yang mengandung unsur tanah jarang adalah mineral apatit, zirkon, monazit, dan mineral pyrochlore. Unsur tanah jarang yang dijumpai pada tujuh contoh sedimen permukaan dasar laut dan 3 contoh bor inti adalah Cerium (15,41 â€“ 16,88 ppm), Lanthanum (5,40 â€“ 6,80 ppm), Ytrium (5,18-5,58 ppm), Zirkonium ( 5,05-5,95 ppm) dan Neodimium 20,25 â€“ 20,95 ppm). Sedimen permukaan dasar laut di perairan Kundur tersusun oleh lanau (Z), lanau pasiran (sZ), kerikil pasiran, lumpur dan pasir. Satuan lanau menutupi hampir 55% dari seluruh daerah penelitian diikuti oleh krikil pasiran , pasir, lumpur dan lanau pasiran. Morfologi permukaan dasar laut sangat bervariasi ada yang landai dengan perubahan kedalaman yang teratur ada juga yang berbentuk lekukan lekukan dan lubang lubang besar kemungkinan akibat dari penambangan pasir. Karakteristik pantainya terdiri dari : pantai berpasir dan pantai berlumpur. Â  Pantai berpasir, berelief sedang (5Â° - 8Â°), tersusun oleh pasir ukuran butir sedang sampai kasar, berwarna kuning kecoklatan. Pantai berlumpur berelief rendah berkisar antaraÂ  (1Â° - 5Â°) dimana pada bagian tepinya ditanami bakau oleh penduduk setempat. Kata kunci: unsur tanah jarang, sedimen permukaan dasar laut, morfologi permukaan dasar laut, dan Pulau Kundur